Karaman İli Ağızlarının Özellikleri ve Sınıflandırılması - Karpuz, Hacı Ömer; Uysal, İdris Nebi (My University, 2010)
İç Anadolu Bölgesi’nin güneyinde yer alan ve Akdeniz Bölgesi’nde de toprakları bulunan Ka- raman, merkez ilçeyle birlikte 6 ilçe ve bunlara bağlı 10 kasaba ve 158 köyden oluşmaktadır. Karaman ağızları, bölgedeki hâkim etnik yapının, Oğuz-Türkmen unsurlarının genel özellikle- rini taşımaktadır. Ancak çalışmamızda tespit ettiğimiz birtakım farklılıklar sonucunda 3 ağız bölgesine ayrılmaktadır. Bunlar; Taşeli Ağız Bölgesi, Ayrancı Ağız Bölgesi, Merkez ve Civarı Ağız Bölgesi.

Karaman; where is located in south of Middle Anatolia and has lands in Akdeniz region, has 6 counties with centric county, 10 towns and 158 villages which belong to 6 counties. Karaman dialects bear common characteristics of Oguz-Turkoman tribes that is dominant ethnic structure in the region but as a result of some differences that we have determined in our study, Karaman dialects are divided three sub-dialect regions. These are; Taşeli Dialect Region, Ayrancı Dialect Region, Center and Around Dialect Region.
Characteristics and Classification of Karaman Dialects
Keywords: Karaman ağızları; ağız; ağız sınıflandırması; alt ağız bölgeleri; Karaman dialects; dialect; classification; dialect classification; sub-dialect regions